Evidence of southwestern distribution of the golden jackal in Prince Mohammed bin Salman Royal Reserve, Saudi Arabia - EHAB EID; JOSH SMITHSON (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Eid E, Smithson J. 2024. Evidence of southwestern distribution of the golden jackal in Prince Mohammed bin Salman Royal Reserve, Saudi Arabia. Biodiversitas 25: 1676-1681. The golden jackal, Canis aureus Linnaeus 1758, is listed as a species of globally Least Concern status by the IUCN; however, throughout the Arabian Peninsula, it is classified as Near Threatened due to the lack of information on its population and threats. Despite beings a widespread species, the information on the golden jackal distribution in Saudi Arabia is derived from limited historical records that have restricted its presence to the Hofuf area, around Al Asfah and Al Jawf in the Northeast, and very recent records in the agricultural areas in Tabuk governorate. In addition, photographic evidence of a juvenile individual was recorded in 2017 around the Jubail area. Here, we report the first confirmed Western distribution extension for Saudi Arabia, located in Prince Mohammed bin Salman Royal Reserve, and the most southwestern distribution worldwide. The jackal was recorded twice, suggesting a passing individual or a resident population, requiring further investigation and research. The presence of suitable ecosystems, habitats, and prey composition supports this. This record is important for Saudi Arabia and the Reserve as it guides the conservation efforts and highlights the importance of systematic surveys to understand the existing population, state, and threats.